A rapidly self-assembling soft-brush DNA hydrogel based on RCA products. Issue 37 (17th April 2019) - Song, Huan; Zhang, Yangzi; Cheng, Ping; Chen, Xu; Luo, Yunbo; Xu, Wentao
Abstract : A rapid self-assembly strategy was developed for fabricating a novel soft-brush DNA hydrogel in one minute by introducing a pair of L-type probes into the RCA products. Abstract : A rapid self-assembly strategy was developed for fabricating a novel soft-brush DNA hydrogel in one minute by introducing a pair of L-type probes into the RCA products. The L-type probes with universality achieved a controllable size and morphology of the DNA hydrogel, providing deeper insight into variability and probability in functional biomaterials.